Non-farm diversification, shocks, capital endowment and incidence of poverty amongst farm households in rural Nigeria - Shehu, Abdulaziz (2015)
The study comprised of three independents objectives that examined the effects of non-farm diversification, shocks and capital endowments on incidence of poverty among farm households in rural Nigeria, using nationwide representative data of Nigerian rural households collected by the Nigerian Bureau of Statistics in collaboration with the World Bank. The first and second objectives utilized the data collected in 2010/2011 while the third objective used the data collected in 2010/2011 and 2012/2013. The first objective examined the determinants of nonfarm diversification (NFD) among the households and its effect on their economic wellbeing. Tobit result showed that NFD significantly depends on household members’ education, social capital, financial capital, community level infrastructures and regional location. Two Stages Least Squares and Propensity Score Matching results also suggested that NFD has a significant positive impact on per capita consumption expenditure of the households. However, the result revealed that non-poor households are benefiting more than the poor ones from NFD. The second objective explored the effect of shocks on household consumption and choice of coping measures. The result suggested that whilst idiosyncratic shocks measured by illness and death had no significant impact on household consumption, covariate shocks specifically climatic and economic shocks had significant negative effect on household consumption. This portrayed the relevance of informal coping strategies in smoothing household consumption. However, the Multivariate Probit result revealed that the informal coping strategies chosen by the households are likely to make them vulnerable to poverty. The third objective assessed the contribution of initial capital endowments to changes in per capital consumption expenditure and incidence of poverty of the households, using Variant Difference Model and Multinomial Logit model respectively. The study found that initial endowments of physical, human, financial and social capital, significantly improved wellbeing and reduced poverty. On this basis, the study recommend for the provision of adequate and essential capital endowments to improve the wellbeing of the households. Overall results obtained are potentially useful to policy makers in developing effective policies that would improve household economic wellbeing as well as reduces Arural poverty.